Conocimientos y aplicación del proceso de atención de enfermería de los profesionales enfermeros del Hospital General Isidro Ayora de Loja - Samaniego León, Edinson Fernando (2022)
The nursing care process (PAE) is a scientific method used in the care practice of nursing professionals, which allows care to be provided with a scientific basis, in a structured, systematic and sequential way, contributing to the recovery of the patient, the present research work whose objective was to analyze the knowledge and application of the nursing care process of the nursing professionals of the Isidro Ayora General Hospital of Loja, it was a descriptive, quantitative crosssectional study, a structured survey previously validated was applied to 130 professionals, finding as results that 41.5% of professionals in the age range of 25 to 35 years, 90.8% are women, 69.2% have professional experience of 1 to 10 years and 16.9% have fourth level complementary studies . In relation to the knowledge that professionals have in relation to the nursing care process, 63.8% correctly identify its definition, 89.2% adequately identify the stages. On the other hand, the knowledge according to the stages of the PAE shows us that 60.8% of the professionals surveyed know the assessment, 74.6% know the diagnoses and planning for the elaboration and organization of the care plan. of the nursing care process, followed by 84.6% know the stage of execution and intervention in the care of said process, and finally 63.1% know about the evaluation. Finally, 69.23% of the professionals do not apply the nursing care process due to influencing factors such as the number of patients, stress and time overload